Financialization, Austerity, and Inclusion in Latin America and the Caribbean - Gautam, Rana S.; Pinheiro, Diogo L.; Wilson, Dwight (Lexington Books, 2023)
Financialization, Austerity, and Inclusion in Latin America and the Caribbean examines the spread of financialization since 1980, highlighting the ideational origins of financialization outside the region, its effects on government budgeting and social inclusion, and options for increased inclusivity. Rana S. Gautam, Diogo L. Pinheiro, and Dwight Wilson argue that rather than a mechanistic implementation of external pressures, financialization is a complex social process with ideational origins in which national-level actors participate. Ultimately, the authors find that deeper financial integration, the expansion of credit, and reliance on international bond markets drives governments to cut certain areas of social spending and drives inequality but ameliorates absolute poverty. There is, therefore, space for agents to mold financialization and its inclusiveness.